Creeboy - Wouters, Teresa (Toronto : James Lorimer & Co. Ltd., 2022)
"Sixteen-year-old Josh is no stranger to gang life. His dad, the leader of the Warriors, a gang on their reserve, is in jail, and Josh's older brother has taken charge. Josh's mom has made it clear the Warriors and their violence aren't welcome in her home--Josh's dad and brother included. She wants Josh to focus on graduating high school. Josh is unsure whether gang life is for him--that is until gang violence arrives on his doorstep. Turning to the Warriors, Josh, now known as 'Creeboy,' starts down the path to becoming a full gang member--cutting himself off from his friends, family and community outside the gang. It's harder than ever for Creeboy to envision a different future for himself. Will anything change his mind?"--Back cover.
School Library Journal, February 2023
4.4.
Young Adult
HL590
Keywords: Gangs -- Juvenile fiction; Teenagers -- Juvenile fiction; Gangs -- Fiction; Teenagers -- Fiction